The Pathophysiological Role of Microglia in Dynamic Surveillance, Phagocytosis and Structural Remodeling of the Developing CNS - Arcuri, Cataldo; Mecca, Carmen; Bianchi, Roberta; Giambanco, Ileana; Donato, Rosario (Frontiers in Molecular Neuroscience, 2017)
In vertebrates, during an early wave of hematopoiesis in the yolk sac between embryonic day E7.0 and E9.0, cells of mesodermal leaflet addressed to macrophage lineage enter in developing central nervous system (CNS) and originate the developing native microglial cells. Depending on the species, microglial cells represent 5-20% of glial cells resident in adult brain. Here, we briefly discuss some canonical functions of the microglia, i.e. cytokine secretion and functional transition from M1 to M2 phenotype. In addition, we review studies on the non-canonical functions of microglia such as regulation of phagocytosis, synaptic pruning, and sculpting postnatal neural circuits. In this latter context the contribution of microglia to some neurodevelopmental disorders is now well established. Nasu-Hakola disease is considered a primary microgliopathy with alterations of the DAP12-TREM2 signaling and removal of macromolecules and apoptotic cells followed by secondary microglia activation. In Rett syndrome Mecp2-/- microglia shows a substantial impairment of phagocytic ability, although the role of microglia is not yet clear. In a mouse model of Tourette syndrome, microglia abnormalities have also been described, and deficient microglia-mediated neuroprotection is obvious. Here we review the role of microglial cells in neurodevelopmental disorders without inflammation and on the complex role of microglia in developing CNS.